Laboratory Predictors of COVID-19 Mortality: A Retrospective Analysis from Tongji Hospital in Wuhan - Ting Zheng; Xinxin Liu; Yingying Wei; Xinlu Li; Bing Zheng; Quan Gong; Lingli Dong; Jixin Zhong (Mediators of Inflammation)
Background. Novel coronavirus disease 2019 (COVID-19), an acute respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), rapidly progressed to a global pandemic. Currently, there are limited effective medications approved for this deadly disease. Objective. To investigate the potential predictors of COVID-19 mortality and risk factors for hyperinflammation in COVID-19. Methods. Retrospective analysis was carried out in 1,149 patients diagnosed with COVID-19 in Tongji Hospital, Wuhan, China, from 1/13/2020 to 3/15/2020. Results. We found significant differences in the rates of hyperuricemia (OR: 3.17, 95% CI: 2.13-4.70; p<0.001) and hypoalbuminemia (OR: 5.68, 95% CI: 3.97-8.32; p<0.001) between deceased and recovered patients. The percentages of hyperuricemia in deceased patients and recovered patients were 23.6% and 8.9%, respectively, which were higher than the reported age-standardized prevalence of 6.2% in Chinese population. Of note, the percentages of both IL-6 and uric acid levels in survived COVID-19 patients were above 90%, suggesting that they might be good specificity for indicators of mortality in COVID-19 patients. The serum level of uric acid (UA) was positively associated with ferritin, TNF-α, and IL-6 but not with anti-inflammatory cytokine IL-10. In addition, the levels of these proinflammatory cytokines in COVID-19 patients showed a trend of reduction after uric acid lowering therapy. Conclusions. Our results suggest that uric acid, the end product of purine metabolism, was increased in deceased patients with COVID-19. In addition, the serum level of uric acid was positively associated with inflammatory markers. Uric acid lowering therapy in COVID-19 patients with hyperuricemia may be beneficial.